Investigation of 244Cm dynamics production in a WWER-1200 reactor for fuel based on 235U and MOX fuel - A.M. Petrovski (Eurasian Journal of Physics and Functional Materials, 2020)
244Cm is a very important nuclide due to the high specific heat release and it may become reasonable to recycle the spent nuclear fuel to extract this isotope. In this work, the dynamics of 244Cm isotope production for the fuel assembly of the WWER-1200 reactor with an enrichment of 4.95% and burnup up to 70 MW · day/kg was calculated using Serpent Monte Carlo code. A similar calculations was performed for MOX-based fuel assembly with the same irradiation characteristics. It has been shown that production of 244Cm in high burnup uranium dioxide fuel, and especially in MOX fuel, reaches a high value, which can cause problems during spent fuel management. The main problems associated with the curium relates to the residual heat and neutron activity.